The State of the Arctic Problems of the Nenets Autonomous Okrug and Prospects of their Solution - Valery P. Zhuravel (Научно-аналитический вестник Института Европы РАН)
The article analyses the first stage of the Nenets Autonomous Okrug’s (NAO) implementation of the 7 tasks set out in the Strategy for Developing the Russian Arctic Zone and Ensuring National Security until 2035. Particular attention is paid to the study of the development of the project for the construction of the deep-water seaport of Indiga and the Sosnogorsk – Indiga railway, transport infrastructure development, including the reconstruction of the seaport and airports. The article analyses the activities on dredging on the Pechora River, construction of a highway, the development of oil and gas condensate mineral resource centers, based on the NAO fields, including the development of new ones. The problem of geological study and development of mineral resource base of solid minerals is considered. The article examines the population dynamics, the experience of Arctic residents, and their tax benefits. The author separately considers the construction of an agroindustrial park and the implementation of export-oriented projects involving deep processing of venison, as well as the issues of developing a tourism cluster in the region. It is concluded that, with the exception of the completion of the Naryan-Mar – Usinsk highway and the intensive development of tourism, the rest of the Arctic projects are at the initial stage, their development hampered by the lack or complete absence of funding.